PENINGKATAN KEMAMPUAN MEMBUAT MEDIA PEMBELAJARAN DENGAN BANTUAN WEBSITE GENIALLY PADA GURU-GURU SMK ISLAM BATU - Rahayu, Wening Patmi; Hidayat, Rachmad; Zutiasari, Ika; Rusmana, Dede; Indarwati, Rila Ayu Agnes; Zumroh, Siti (Transpublika Publisher, 2023)
The rapid development of information technology has resulted in a transformation in the educational paradigm, forcing educators to reformulate their learning models. In this context, technology integration becomes imperative, encouraging teachers to utilize technological tools in the learning process. Despite the abundance of free online learning resources, it remains crucial to align them with real classroom dynamics. In response to this change, an innovative workshop was held at SMK Islam Batu, with the main objective of strengthening educators' competencies in the utilization of technology in learning, particularly through the Genially platform. The workshop explored teachers' skills in technology utilization, with an emphasis on using Genially as a tool to produce interactive and engaging learning content. The results of this workshop were impressive. Teachers not only improved their understanding of technology, but were also able to apply this knowledge effectively in their learning. The positive impact of this change in approach can also be seen in the quality of learning at SMK Islam Batu, where learning becomes more powerful, engaging and interactive. The success of this workshop has wider implications that extend beyond the school itself.